National defense and public policy in border governance: A strategic security perspective - Suadnyana, I Nyoman; Supriyadi, Asep Adang; Irwanto, Bambang; Aritonang, Sovian; Ghazalie, Ghazalie (Jurnal Praksis dan Dedikasi Sosial, 2025)
Indonesia’s border areas play a vital role in safeguarding national sovereignty and stability, particularly in facing cross-border security challenges such as smuggling, human trafficking, piracy, and overlapping territorial claims. This research aims to analyze national security strategies in border area management through a public policy approach. Using a descriptive qualitative method based on literature review, the study explores various strategies including military strengthening, defense diplomacy, the use of advanced technologies such as satellites, drones, and artificial intelligence, as well as the integration of economic and social policies in border regions. The findings reveal that effective border management requires a multidimensional approach involving synergy between the defense sector, local governments, civil society, and international cooperation. Investment in surveillance infrastructure, institutional reform, and the development of border economic zones are essential to build a resilient and sustainable security system. This study recommends a collaborative, strategically adaptive policy framework that responds to global geopolitical dynamics to protect Indonesia’s sovereignty and promote the welfare of communities in border areas.